The Apelin/APJ System in Psychosis and Neuropathy - Shuang-Yu Lv; Wei-Dong Chen; Wei-Dong Chen; Yan-Dong Wang (Frontiers Media S.A., 2020)
Apelin, an endogenous neuropeptide, has been identified as the cognate ligand for the G-protein-coupled receptor APJ. Apelin, APJ messenger RNA, and protein are widely expressed in the central nervous system and peripheral tissues of humans and animals. The apelin/APJ system has been implicated in diverse physiological and pathological processes. The present article reviews the progress of the latest research investigating the apelin/APJ system in pain, depression, anxiety, memory, epilepsy, neuroprotection, stroke, and brain injury and protection, and highlights its promising potential as a therapeutic target for treatment of psychosis and neuropathy.